THE PROTAGONIST’S EXPECTATION IN DEWI LESTARI’S PAPER BOAT - Ain, Qurratul; Sahri, Zulfan (Universitas Islam Sumatera Utara, 2025)
Expectation is a positive mental state about the ability to achieve future goals. The Paper Boat novel by Dewi Lestari is one of the literary works that has a positive attitude about expectation. This thesis aims to identify the expectations of the protagonist and how the protagonist achieves her expectations in the Paper Boat novel by Dewi. This study uses a qualitative descriptive research method to process and analyze the data. This study explores the way of life and life lessons for a better life goal. The results of this study indicate the expectations of the protagonist pertaining to becoming a writer, making a work, namely a fairy tale book, which includes the hard work and patience seen in the protagonist Kugy, and marrying the person she loves. As for the dominant expectation is the protagonist who really wants to be a writer, because of the optimistic attitude contained in the protagonist, all her expectations come true.